How is Technology Positioned in the Implementation of SSI-Based Learning? - Ariyati, Eka; Yokhebed, Yokhebed; Marlina, Reni (Jurnal Pendidikan Progresif, 2025)
How is Technology Positioned in the Implementation of SSI-Based Learning? Objectives: Socio-Scientific Issues (SSI)-based learning is an educational approach that combines scientific content with ethical, social, and real-world issues. This learning model is significantly influenced by technology, which enhances student engagement, facilitates access to a variety of information sources, and offers interactive and immersive experiences. This research endeavors to conduct a comprehensive analysis of the position of technology in SSI-based learning, with a particular emphasis on its functions, forms of application, and effects. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method was employed to conduct the Systematic Literature Review (SLR). Keywords associated with "Social-Scientific Issues" and "technology in education" were implemented during a literature search of Scopus-indexed journals from 2016 to 2025. The initial search identified 399 articles, which were subsequently filtered through the identification, screening, eligibility, and inclusion processes, culminating in 39 eligible articles. Articles published in English, indexed in Scopus, and specifically addressing the intersection of SSI and technology are included in the inclusion criteria. In order to investigate patterns, keyword trends, and thematic clusters, articles were subjected to bibliometric analysis using RStudio–Biblioshiny and VOS viewer. Findings: These findings categorize the role of technology in two main ways: (1) Direct implementation in SSI-based teaching, such as Augmented Reality (AR), Virtual Reality (VR), Artificial Intelligence (AI), web-based platforms, and educational games; and (2) Integration of technology in broader pedagogical approaches, including STEM, STEAM, STS, and Computational Thinking (CT). Conclusion: Technology serves variety functions: it acts as a source of information, a collaborative tool, a platform for virtual experimentation, and a medium for communicating ideas. This review highlights the growing significance of technology in shaping effective, critical, and contextually rich SSI-based learning in the digital age. Keywords: socio-scientific issues (ssi), technology, digital application, systematic literature review.